The Cellular DExD/H-Box RNA Helicase UAP56 Co-localizes With the Influenza A Virus NS1 Protein - Chiba, Shiho; Hill-Batorski, Lindsay; Neumann, Gabriele; Kawaoka, Yoshihiro (Frontiers in Microbiology, 2018)
UAP56, a member of the DExD/H-box RNA helicase family, is essential for pre-mRNA splicing and mRNA export in eukaryotic cells. In influenza A virus-infected cells, UAP56 mediates viral mRNA nuclear export, facilitates viral ribonucleoprotein complex formation through direct interaction with the viral nucleoprotein, and may indirectly affect antiviral host responses by binding to and/or facilitating the activation of the antiviral host factors MxA and PKR. Here, we demonstrate that UAP56 also co-localizes with the influenza A viral NS1 protein, which counteracts host cell innate immune responses stimulated by virus infection. The UAP56-NS1 association relies on the RNA-binding residues R38 and K41 in NS1 and may be mediated by single-stranded RNA. UAP56 binding to NS1 does not affect the NS1-mediated downregulation of cellular innate immune pathways in reporter gene assays, leaving in question the exact biological role and relevance of the UAP56-NS1 association.